2010
DOI: 10.1590/s0104-56872010000400030
|View full text |Cite
|
Sign up to set email alerts
|

Processamento temporal auditivo: relação com dislexia do desenvolvimento e malformação cortical

Abstract: Background: temporal auditory processing and developmental dyslexia. Aim: to characterize the temporal auditory processing in children with developmental dyslexia and to correlate findings with cortical malformations. Method: twenty school-aged children, ranging in age from 8 to 14 years were evaluated. These children were divided into two groups: the experimental group (EG) was composed by 11 children (eight were male) with developmental dyslexia and the control group (CG) was composed by nine normal children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
2
10
0
8
Order By: Relevance
“…The authors found significant differences for the assessment of temporal (central) AP between the groups, and a correlation between the test performance and words and non-words reading skills. Similar results were also found in other two studies that investigated temporal AP in children with dyslexia and in a control group (4,23) . The studies concluded that a deficit in the AP for short sounds may affect the perception of speech sounds an lead to a phonological awareness deficit and further reading problems.…”
Section: Discussionsupporting
confidence: 90%
“…The authors found significant differences for the assessment of temporal (central) AP between the groups, and a correlation between the test performance and words and non-words reading skills. Similar results were also found in other two studies that investigated temporal AP in children with dyslexia and in a control group (4,23) . The studies concluded that a deficit in the AP for short sounds may affect the perception of speech sounds an lead to a phonological awareness deficit and further reading problems.…”
Section: Discussionsupporting
confidence: 90%
“…Histologic characteristics of these malformations strongly suggested a genesis in prenatal development, since they revealed abnormal placement of neurons within cortical layers (i.e., malformations including ectopias and microgyria). More recently, similar findings have been reported for individuals with developmental language impairment (Oliveira et al, 2007; Brandão-Almeida et al, 2008; Boscariol et al, 2010, 2011). Initially, these findings were thought to implicate a relationship between clinical diagnosis and specific disruption of fronto-temporal regions critical to language processing (since the distribution of anomalies in the affected brains was substantially greater in left perisylvian areas).…”
Section: Auditory Processing Deficits and Language Disability: Human supporting
confidence: 77%
“…Individuals with this disorder have normal nonverbal intelligence, but score more than a standard deviation below their peers on reading tests [1], [3], [4]. Children and adults with dyslexia typically have deficits in phoneme perception and manipulation [5]–[8]. Even before learning to read, neural activation during phonological processing is impaired in young children at risk for dyslexia [9], which suggests that the neural abnormalities responsible for dyslexia are present from birth and do not reflect experience-dependent processes [10].…”
Section: Introductionmentioning
confidence: 99%